LTP in a Culture Dish - J.F. MacDonald; William Ju; Yu Tian Wang (The Scientific World Journal)
The “aging” of populations in the developed world is rapidly altering demographics and presents a number of challenges for science and medicine. Foremost among these challenges is the need to enhance the quality of life for this “aging” majority. Paradoxically, improved prevention and treatment of diseases will only increase the number of individuals who will lose quality of life because of cognitive deficits in learning and memory. Such cognitive deficits are particularly vexing in societies where the ability to deal with information technology has become an increasing necessity. Understanding how the human brain encodes and stores information becomes critical in designing required therapeutic strategies.